UPAYA GURU BIMBINGAN DAN KONSELING DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI MADRASAH ALIYAH NEGERI 2 MODEL MEDAN - Eka Lestari (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
The purpose of this research how the character standards of students in the Aliyah Negeri 2 Medan Model Madrasah then find out what kind of policies apply in the Madrasah and know how teachers guidance and counseling efforts in shaping the character of students in the Aliyah Negeri 2 Model Medan Madrasah such as improve the attitudes and behaviors of students so that they have a personality that is intelligent and Islamic character.Â Methodologically, this research is a field research with a phenomenological qualitative approach, the primary data source in this study is guidance and counseling teachers, students and principals. Data collection techniques used by interviews, observation and documentation. In analyzing research using data analysis techniques, data reduction, and drawing conclusions after that the validity of the data is examined using credibility, transferability, dependability and confirmability.Â The results of this study can be concluded by students in Madrasah Aliyah Negeri 2 Model Medan (1) with Islamic character. (2) policies applied: discipline and smiling greetings, obliging congregational prayers and duha prayers, reciting Asmaul Husna during morning apple and muroja'ah surah al-quran before starting the lesson. (3) provide material classically or individually, pay attention to students outside of study hours and provide additional activities as a form of habituation.Â The conclusion of this study is the efforts made by guidance and counseling teachers in shaping the character of students by enforcing the rules and policies that apply in Madrasah Aliyah Negeri 2 Medan Model, as well as providing material and understanding of the character that students must have in a classical or individual way.